1991
DOI: 10.1002/mc.2940040614
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of 2‐acetylaminofluorene‐and 3‐methylcholanthrene‐mediated induction of multidrug resistance and cytochrome P450IA gene family expression in primary hepatocyte cultures and rat liver

Abstract: Previous studies by this laboratory have indicated that expression of the multidrug resistance (mdr) gene can be increased in vivo by exposure to a variety of xenobiotics. Because of the nature of these compounds, it was proposed that mdr gene expression might, at least in part, be regulated by the arylhydrocarbon (Ah) receptor. In the present study, we used a primary hepatocyte culture model to examine the relationship between induction of cytochrome P450IA and mdr expression in vitro. Both 3-methylcholanthre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(81 citation statements)
references
References 57 publications
1
79
1
Order By: Relevance
“…Previously we and others have demonstrated that several xenobiotics are able to induce the mdr gene expression (33,36,37,42). One of the mnost potent mdr inducers in the rat is 2-acetylaminofluorene (2-AAF).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Previously we and others have demonstrated that several xenobiotics are able to induce the mdr gene expression (33,36,37,42). One of the mnost potent mdr inducers in the rat is 2-acetylaminofluorene (2-AAF).…”
Section: Resultsmentioning
confidence: 93%
“…One of the mnost potent mdr inducers in the rat is 2-acetylaminofluorene (2-AAF). In rat liver and isolated hepatocytes, AAF is able to induce transcription of the mndrl genes and thus elevate their expression measured at both the mRNA and protein levels (37). In monkeys AAF is also able to induce mdr expression though the effect is less and more variable than that seen in the rat (Gant et al, unpublished data).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…For example the nuclear run on assay has been used to show that transcription of the ABCB1 gene can be increased after chemical exposure in the liver [28]. It should be possible to undertake such an analysis on a global scale using a microarray.…”
Section: Array Comparative Genome Hybridisation (Arraycgh)mentioning
confidence: 99%
“…Double immunofluorescence microscopy with the carcinogens, as well as mechanically and chemically induced keratin polyclonal antibody and the mab C219 at this cholestasis, have been previously shown to induce the exprestime point revealed a complete loss of Pgp staining in sion of mdr genes and their products, Pgp, in rodent and affected cells, although remaining hepatocytes with un-nonhuman primate liver. [15][16][17][18][19][20][21] Pgp is often overexpressed in altered KIF meshwork showed a strong reaction with tumor cells exhibiting resistance to the cytotoxic effects of a the C219 antibody. Northern blot analyses revealed a number of structurally and functionally unrelated drugs.…”
mentioning
confidence: 99%